2012
DOI: 10.1590/s2236-89062012000100006
|View full text |Cite
|
Sign up to set email alerts
|

Water deficit affects wood vessels of Croton floribundus Spreng. in different vegetation types, São Paulo State, Brazil

Abstract: -(Water defi cit affects wood vessels of Croton fl oribundus Spreng. in different vegetation types, São Paulo State, Brazil). In this paper we showed that water defi cit affects the wood vessels of Croton fl oribundus in fi ve areas with different vegetation types: Rain Forest, Semi-deciduous Forest and Woody Savanna. We concluded that variations in the vessels are due especially to water defi cit and the number of months with water defi cit. Larger diameter vessels occurred in areas with higher water defi cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(11 reference statements)
1
1
0
Order By: Relevance
“…Thus, comparisons are made with other species of the genus. Using that basis of comparison, the wood anatomy of Croton piptocalyx generally agrees with that of other species of the genus such as described in the literature, including Croton urucurana (Luchi, 2004), some other 159 species of the genus (Wiedenhoeft, 2008) and Croton floribundus (Longui et al, 2012). However, as a result of tree age and species differences, the quantitative data do vary.…”
Section: Macro and Microscopic Anatomical Description Of Croton Piptosupporting
confidence: 68%
See 1 more Smart Citation
“…Thus, comparisons are made with other species of the genus. Using that basis of comparison, the wood anatomy of Croton piptocalyx generally agrees with that of other species of the genus such as described in the literature, including Croton urucurana (Luchi, 2004), some other 159 species of the genus (Wiedenhoeft, 2008) and Croton floribundus (Longui et al, 2012). However, as a result of tree age and species differences, the quantitative data do vary.…”
Section: Macro and Microscopic Anatomical Description Of Croton Piptosupporting
confidence: 68%
“…The wood of some species of this genus have already been studied (Luchi, 2004;Wiedenhoeft, 2008;Wiedenhoeft et al, 2009;Longui et al, 2012;Novello et al, 2012;Siegloch et al, 2012). However, no studies in the literature have reported on C. piptocalyx wood.…”
Section: Introductionmentioning
confidence: 99%